Perspectives of a free trade agreement between Guatemala and China - Delgado, Joel (KDI School, 2011)
China is an emerging major player from which Guatemala could benefit by entering a free trade agreement to enjoy a preferential access to this important economy. However, it is important to consider that Guatemala has diplomatic relations with Taiwan, which is a thorn in China’s eye, and supports the island´s sovereignty. Another of Guatemala´s international trade priority is to complete the Central American regional economic integration. The region’s integration efforts have led the Central American countries to engage in a joint negotiation process with prospective partners outside the region. But this requires Guatemala to perform a delicate balancing act in her trade negotiation with the Republic of China. Before Guatemala engages in a negotiation with China, it has to consider the possible advantages and disadvantages that this decision could represent and how this would affect some key elements of Guatemala´s trade and foreign policy like: the country´s foreign policy principles; Guatemala’s commitment with the Central American economic integration; the historical relation with Taiwan and Costa Rica´s experience on their negotiation of a free trade agreement with China. There could be another option for Guatemala and the key is the Economic Cooperation Framework Agreement that China has established with Taiwan, it might very well be the tool that Guatemala could use to improve its trade conditions with China without having to abandon Taiwan.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Guatemala--China